The Factors Affecting The Cost Estimating In Pre-Construction Process - Mohamad, Yusmawati (Universiti Sains Malaysia, 2006)
Cost is important asset to determine the budget of the construction project. Cost estimating should be determined before go to the next step in construction stage. It is useful to make sure the project is feasible to build or develop. Cost estimating is also important in determining the budget of the construction’s project. The estimates made in the early phases of a project are particularly important because they affect the most basic decisions about a project: whether it will be undertaken at all; how large it will be; how it elaborate, sophisticated and durable it will be; and how much it will cost.